Donepezil prevents RANK-induced bone loss via inhibition of osteoclast differentiation by downregulating acetylcholinesterase - Tsuyoshi Sato; Yuichiro Enoki; Yasushi Sakamoto; Kazuhiro Yokota; Masahiko Okubo; Masahito Matsumoto; Naoki Hayashi; Michihiko Usui; Shoichiro Kokabu; Toshihide Mimura; Yoshihiko Nakazato; Nobuo Araki; et al. (Heliyon, 2015)
Objective: Donepezil, an inhibitor of acetylcholinesterase (AChE) targeting the brain, is a common medication for Alzheimer's disease. Interestingly, a recent clinical study found that administration of this agent is associated with lower risk of hip fracture independently of falling, suggesting its direct effect on bone tissues as well. AChE has been reported to be involved in osteoblast function, but the role of AChE on osteoclastogenesis still remains unclear. We analyzed the effect of AChE and donepezil on osteoclastogenesis in vivo and in vitro. Methods: Cell-based assays were conducted using osteoclasts generated in cultures of murine bone marrow macrophages (BMMs) with receptor activator of nuclear factor-kappa B ligand (RANKL). The effect of donepezil was also determined in vivo using a mouse model of RANKL-induced bone loss. Results: Recombinant AChE in BMMs cultured with RANKL further promoted RANKL-induced tartrate-resistant acid phosphatase (TRAP)-positive osteoclast differentiation. RANKL also upregulated AChE expression in BMMs. RNA interference-mediated knockdown of AChE significantly inhibited RANKL-induced osteoclast differentiation and suppressed gene expression specific for osteoclasts. AChE upregulated expression of RANK, the receptor of RANKL, in BMMs. Donepezil decreased cathepsin K expression in BMMs and the resorptive function of osteoclasts on dentine slices. Donepezil decreased RANK expression in BMMs, resulting in the inhibition of osteoclast differentiation with downregulation of c-Fos and upregulation of Id2. Moreover, administration of donepezil prevented RANKL-induced bone loss in vivo, which was associated with the inhibition of bone resorption by osteoclasts. Conclusions: AChE promotes osteoclast differentiation in vitro. Donepezil inhibits osteoclast function in vitro and prevents bone loss by suppressing bone resorption in vivo, suggesting the possibility that donepezil reduces fracture risk in patients with Alzheimer's disease.